2010
DOI: 10.1167/iovs.09-5139
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Retinal Vascular Wall Dimensions

Abstract: Transgenic αSMA-GFP expression in murine vessel wall components allowed quantification of retinal vessel outer diameters in vivo. Although arterioles and venules differ in lumen and vessel wall width, they share a common outer diameter, leading to an AVR(od) close to unity. Because vessel walls are primary targets in common hypertensive and metabolic diseases, αSMA-GFP transgenic mice may prove valuable in the detailed assessment of such disorders in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
3
14
1
Order By: Relevance
“…Contrary, Chui et al recently postulated that vessel walls are detectable using adaptive optics cSLO [37]. Additionally, our data shows AVR values higher than 0.8 in cSLO IR imaging in both groups, which gives rise to doubts whether cSLO IR in fact measures inner vessel diameters considering that AVR values of about 2/3 for the inner vessel diameter were reported previously [34], [38]. We use the term ‘maximum vessel diameter’ for the diameter measured in cSLO IR images.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary, Chui et al recently postulated that vessel walls are detectable using adaptive optics cSLO [37]. Additionally, our data shows AVR values higher than 0.8 in cSLO IR imaging in both groups, which gives rise to doubts whether cSLO IR in fact measures inner vessel diameters considering that AVR values of about 2/3 for the inner vessel diameter were reported previously [34], [38]. We use the term ‘maximum vessel diameter’ for the diameter measured in cSLO IR images.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly to funduscopy, the authors postulate that native cSLO IR only captures inner vessel diameter, while vessel outer diameters as well as vessel walls remain undetectable [34].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the diameters of retinal blood vessels by means of various methods had been previously reported. [1][2][3][4][5][6][7] As mentioned earlier, 2-dimensional and 3-dimensional automated segmentation of retinal blood vessels was successfully accomplished. 9,10 The results of those studies have shown that retinal vessel diameter can be measured using automated segmentation of blood vessels from OCT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Fundus color photographs, 1-3 fluorescein angiograms, 4 linear image sensor on a fundus camera, 5 the Zeiss retinal vessel analyzer (a fundus camera-based system), 6 and scanning laser ophthalmoscope with angiography 7 have all been used to evaluate the diameters of retinal vessels, with fundus color photography emerging as the most popular among them. A computerized program was later developed to analyze the vessel measurements in those photographs.…”
mentioning
confidence: 99%
“…Several methods have been described for the measurement of retinal vessel diameters, most of which use retinal photography and computer-assisted image analysis to characterize and quantify subtle variations and abnormalities in the retinal vasculature [2-4, 11, 12]. In addition, fluorescein angiograms (FA) [13], indocyanine green angiography [14], retinal vessel analyzers [3,15], and scanning laser ophthalmoscopes [14] have all been used to evaluate the diameters of retinal vessels. Optical coherence tomography (OCT) is an imaging modality capable of providing high-resolution, crosssectional images of the neurosensory retina.…”
Section: Introductionmentioning
confidence: 99%